A qualitative analysis of perceptions of various stakeholders on combining nutrition-sensitive agricultural interventions with the taxation on sugar-sweetened beverages (SSBs) to improve overall health and nutrition in South Africa - Kaltenbrun, Tayla Ashton (Stellenbosch : Stellenbosch University, 2020)
Thesis (MNutr)--Stellenbosch University, 2020.